2010
DOI: 10.1007/978-1-60761-984-0_2
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolds for Tissue Engineering and 3D Cell Culture

Abstract: In tissue engineering applications or even in 3D cell cultures, the biological cross talk between cells and the scaffold is controlled by the material properties and scaffold characteristics. In order to induce cell adhesion, proliferation, and activation, materials used for the fabrication of scaffolds must possess requirements such as intrinsic biocompatibility and proper chemistry to induce molecular biorecognition from cells. Materials, scaffold mechanical properties and degradation kinetics should be adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
257
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(277 citation statements)
references
References 91 publications
0
257
0
4
Order By: Relevance
“…The scaffold functions as the in vivo ECM by providing structural and functional microenvironment (i.e., ''niche'') for cell growth, migration, and differentiation. [9][10][11][12] Although the composition of ECM environment is unique to each tissue, the major components of ECMs are collagens, fibronectin, laminin, and various types of glycoaminoglycans and proteoglycans. 13 ECM, together with growth factors, cytokines, and interactions with other cell types, renders the biological and physical cues that dictate MSC function and overall fate.…”
Section: Introductionmentioning
confidence: 99%
“…The scaffold functions as the in vivo ECM by providing structural and functional microenvironment (i.e., ''niche'') for cell growth, migration, and differentiation. [9][10][11][12] Although the composition of ECM environment is unique to each tissue, the major components of ECMs are collagens, fibronectin, laminin, and various types of glycoaminoglycans and proteoglycans. 13 ECM, together with growth factors, cytokines, and interactions with other cell types, renders the biological and physical cues that dictate MSC function and overall fate.…”
Section: Introductionmentioning
confidence: 99%
“…It was confirmed that design of degradation scaffold plays an important role due to appropriate environment for the cell to adhere, proliferate, differentiate and generate an extracellular matrix for tissue regeneration [15].…”
Section: Figure 5 Fibroblast Proliferation On Scaffoldsmentioning
confidence: 87%
“…Les procĂ©dĂ©s d'ingĂ©nierie tissulaire font appel, dans la plupart des cas, Ă  des matĂ©riaux poreux, structure-support pour la croissance (scaffolds). La constitution de ces scaffolds est essentielle pour assurer la multiplication et la diffĂ©renciation des cellules [5]. Le scaffold pourra aussi contenir des vecteurs d'expression de gĂšnes ou des facteurs de croissance cellulaire ou encore d'autres molĂ©cules susceptibles de guider les cellules et d'induire leur diffĂ©rencia-tion.…”
Section: E Fattalunclassified